Quantitative HPLC analysis of flavonoids and evaluation of antioxidant activity in two organs of Salvia tebesana Bunge - Maryam Babaie; Monireh Cheniany; Ali Ganjeali; Jamil Vaezi (Institue of Medicinal Plants, ACECR, 2023)
Background: Salvia tebesana Bunge, as an important herb in folk medicine, is distributed in limited geographical locations in the Middle East. Objective: In this study, three protic solvents, 80 % methanol, 80 % ethanol, and double-distilled water, were investigated to recover the phenolic constituents from S. tebesana extracts. Methods: The antioxidant activity (estimated by total antioxidant capacity, DPPH, and FRAP radical scavenging assays) and the content of phenols, ortho-diphenols, phenolic acids, flavonoids, flavonols, and proanthocyanidins of extracts from leaves and stems of S. tebesana were investigated. After selecting the best solvent, the samples were assayed for individual flavonoid compounds (apigenin, quercetin, myricetin, and rutin) by HPLC-PDA. Results: Different plant extracts demonstrated strong radical scavenging activities, and the leaf extract obtained by 80% methanol showed the highest antioxidant capacity. The same extract also exhibited the most ortho-diphenol, phenolic acid, flavonoid, and proanthocyanidin contents (1598.5 ± 46.2, 742.2 ± 41.3, 487.6 ± 21.9, and 350.1 ± 31.4 mg 100 g-1 DW sample, respectively), while 80 % ethanol extract of leaves gave the most phenolic and flavonol contents (2299.2 ± 47.3 and 359.1 ± 42.3 mg 100 g-1 DW sample, respectively). The high level of flavone apigenin (466.1 ± 11.1 µg g-1 DW) and flavonol rutin (348.6 ± 10.02 µg g-1 DW) were also found in methanol extracts of leaves and are reporting for the first time in S. tebesana. Conclusion: These findings warrant that S. tebesana, in particular the leaves, can be suggested as a natural preservative in dietary and medical applications with the potential to reduce oxidative stress.